Postcesarean Splenic Torsion - Yu-Hui Huang; Chin-Yuan Hsu; Yi-Fang Chang; Chih-Ping Chen (Elsevier, 2006)
Objective: Splenic torsion is an exceedingly rare complication in pregnancy. We present a case of acute splenic torsion that manifested after cesarean section and which was successfully treated with laparotomy with splenectomy and partial pancreatectomy. Case Report: A 35-year-old, gravida 7, para 1, aborta 5, woman presented at our hospital for planned cesarean section at 38 weeks of gestation. Thrombocytopenia was noted antenatally and enlarged spleen with smooth surface and contour was observed at the conclusion of cesarean section. One day after delivery, dyspnea and left upper abdominal pain developed. Abdominal computed tomography showed a huge abscess in the left anterolateral abdomen and bilateral pleural effusion. Acute splenic torsion was highly suspected, but the patient refused surgical intervention until the condition exacerbated 21 days after delivery. Splenic pedicle strangulation with thrombosis, a severely ischemic spleen with rupture and distal pancreatic necrosis were noted during emergent laparotomy. She had an uneventful recovery and was discharged 5 days after left splenectomy and partial pancreatectomy. Conclusion: Splenic torsion is a rare cause of acute abdominal pain during pregnancy or postpartum, and the symptoms vary depending on the degree of torsion. Early involvement of many complementary specialty services enabled early recognition of this rare entity and timely definitive treatment.